Undergraduate Students’ Evaluation of Internships in Special Education Programs in Saudi Universities - Al-Asiri, Hawazen (Amazonia Investiga, 2022)
This study aimed to identify the views of undergraduate students on internships in special education programs in Saudi universities and delineate any statistically significant differences in the students’ views attributable to gender, specialization, university, and grade point average. The study also attempted to investigate the extent to which education outcomes meet the labor market requirements of Saudi Arabia Vision 2030 from the perspective of internship students in special education programs in Saudi universities. To this end, a descriptive approach was applied, using a questionnaire to collect the study data. The study sample consisted of 271 internship students of special education in Saudi universities. The results revealed a high rating level for internships from the perspective of special education students. There were statistically significant differences in the ratings based on gender, with female students reporting better on the academic supervisor dimension. Students specializing in learning disabilities also shared better ratings than those in the autism program, and students with “Excellent” grades reported higher ratings of internship than those with “Good” grades. Overall, there was a high level of compatibility between educational outcomes and the requirements of the labor market stipulated by Vision 2030.